Comparison of two PET radioligands, [11C]FPEB and [11C]SP203, for quantification of metabotropic glutamate receptor 5 in human brain - Lohith, Talakad G; Tsujikawa, Tetsuya; Siméon, Fabrice G; Veronese, Mattia; Zoghbi, Sami S; Lyoo, Chul Hyoung; Kimura, Yasuyuki; Morse, Cheryl L; Pike, Victor W; Fujita, Masahiro; Innis, Robert B (Journal of cerebral blood flow and metabolism, 2017)
Of the two 18F-labeled PET ligands currently available to image metabotropic glutamate receptor 5 (mGluR5), [18F]FPEB is reportedly superior because [18F]SP203 undergoes glutathionlyation, generating [18F]-fluoride ion that accumulates in brain and skull. To allow multiple PET studies on the same day with lower radiation exposure, we prepared [11C]FPEB and [11C]SP203 from [11C]hydrogen cyanide and compared their abilities to accurately quantify mGluR5 in human brain, especially as regards radiometabolite accumulation. Genomic plot was used to estimate the ratio of specific-to-nondisplaceable uptake (BPND) without using a receptor blocking drug. Both tracers quantified mGluR5; however [11C]SP203, like [18F]SP203, had radiometabolite accumulation in brain, as evidenced by increased distribution volume (VT) over the scan period. Absolute VT values were ∼30% lower for 11C-labeled compared with 18F-labeled radioligands, likely caused by the lower specific activities (and high receptor occupancies) of the 11C radioligands. The genomic plot indicated ∼60% specific binding in cerebellum, which makes it inappropriate as a reference region. Whole-body scans performed in healthy subjects demonstrated a low radiation burden typical for 11C-ligands. Thus, the evidence suggests that [11C]FPEB is superior to [11C]SP203. If prepared in higher specific activity, [11C]FPEB would presumably be as effective as [18F]FPEB for quantifying mGluR5 in human brain.